Longman preparation course for the TOEFL test - Phillips, Deborah (White Plains, N.Y Longman, 1996)
This course gives students the skills, strategies, practice and confidence they need to increase their scores on all sections of the TOEFL Test, including the Test of Written English. This edition reflects the revised TOEFL, first administered in July 1995
Keywords: English language Textbooks for foreign speakers; Language Study guides